A Study on Practices and Pitfalls of Human Resource in K12 Schools of Punjab - Dr. Mridula Mishra, Neeraj Mohan Puri (Mathematical Statistician and Engineering Applications, 2022)
Education plays a linchpin role to determine the socio-economic status of an individual. Progress of every economy by and large is dependent upon its competent workforce. K12 schools lay the foundation of future human capital. For this experienced and diligent educator are required. This study is done to identify present Human Resource Practices and the challenges faced by K12 schools of Punjab. Sample size of this study is 132, self structured questionnaire is used to collect data. Cronbach Alpha is applied to confirm the validity of the variables under study. Stratified Sampling technique is used. Thematic Analysis is used to achieve the objectives. Most of the K12 schools have fixed HR practices on recruitment and selection, training and development, performance appraisal and retention at place and the major challenges faced are absence of any analytics and metrics to take informed decisions.